Malaysian medical tourism communication in shaping Indonesian public opinion - Trie Damayanti; Susanne Dida; Dadang Rahmat Hidayat; Sung Kyum Cho (Jurnal Kajian Komunikasi, 2021)
Malaysia is developing medical tourism as a tourism industry aimed at foreign tourists. For this tourism industry, Malaysia makes Indonesia as one of the tourist targets that are expected to bring foreign exchange for the country. Data shows that Indonesians are the largest contributor of tourists visiting Malaysia for treatment. This shows the trust of Indonesian citizens in the health services of the neighboring country. The concept of tourism communication mentions that to achieve the success of medical tourism at least several things are needed that can be fulfilled, namely: competitive prices, available human resources for medical services, the existence of research and development of medical capabilities, infrastructure development, state institutions that support medical tourism, a supportive market economy, the ability to bring together present-day medical technology with traditional, and tourist attractions. Things that are built through tourism communication itself are expected to produce a public opinion about tourist destinations, where this public opinion is the first step in the formation of a country’s brand. This study uses a survey method, which involves about 96 respondents who are on the islands of Sumatra and Java. Use descriptive analysis techniques to explore results. The results obtained by not all components in tourism communication for medical tourism are seen as influencing Indonesian opinion on Malaysian medical tourism. The strangest thing that comes to the view of the Indonesian people is Malaysia’s credibility on health services, the credibility of doctors, the equipment used, the ability to convey information, adequate infrastructure, and the beauty of tourist destinations. Most opinions state that Malaysia can show as a country that successfully develops tourist confidence in the health services offered. The implication of this research is that the opinion of foreign nationals in a country greatly affects the image of that country in the international world.